2008
DOI: 10.1007/s00264-008-0586-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of accuracy of an electromagnetic computer-assisted navigation system in total knee arthroplasty

Abstract: The objective of this study was to develop a method to assess the accuracy of an electromagnetic technology image-free navigation system for total knee arthroplasty in a leg with normal or abnormal mechanical alignment. An acrylic phantom leg was constructed to simulate tibia and femur deformation. Determination of actual leg alignment was achieved using a digital caliper unit. In the setting of normal alignment, the mean error of the system characterised as the difference between the measured computer navigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Our experience was that in the presence of ferrous materials the system would go 'blind' and prior to loss of signal, no unexplained change in the system readout values was noted. Other in vitro and in vivo studies looking at the results of electromagnetic navigation have confirmed that system accuracy is not problematic, with good results comparable to infra-red systems [35,40,41]. Two clinical studies have compared the electromagnetic technique directly with traditional infra-red navigation systems and found similar, high degrees of accuracy [42,43], although the numbers in these studies were small.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Our experience was that in the presence of ferrous materials the system would go 'blind' and prior to loss of signal, no unexplained change in the system readout values was noted. Other in vitro and in vivo studies looking at the results of electromagnetic navigation have confirmed that system accuracy is not problematic, with good results comparable to infra-red systems [35,40,41]. Two clinical studies have compared the electromagnetic technique directly with traditional infra-red navigation systems and found similar, high degrees of accuracy [42,43], although the numbers in these studies were small.…”
Section: Discussionmentioning
confidence: 86%
“…Some of our increased time was associated with data collection for the study to assist in post-operative analysis but the majority results from array insertion, landmark registration and inevitable, although uncommon software glitches. This increase in surgical time allied to the additional costs of hardware, software and disposables required to carry out the surgery all put pressure on navigation techniques to deliver better surgical outcomes [11,[14][15][16][17]19,[30][31][32][33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason a different, independent system (3D measurement device) was used in this study to assess the precision of the navigation system. Pitto et al [17] used the same method to assess the accuracy of an infrared CAS navigation system in legs with abnormal mechanical axes and to determine accuracy of CAS based on electromagnetic technology [18].…”
Section: Discussionmentioning
confidence: 99%
“…Given the precise algorithm which allows accurate measurement of mechanical axis, computer navigation is now considered to be the new gold standard for the purpose. Recently, Graydon et al [6] evaluated the in vitro use of a navigation system based on electromagnetic technology, reporting accuracy similar to infrared-based navigation systems for total knee arthroplasty.…”
Section: Resultsmentioning
confidence: 99%